THE ROLE OF THE KUBU RAYA REGENCY LIBRARY IN PROMOTING A CULTURE OF LITERACY - Sulisdiani, Indah; Martinus (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
The role of the Kubu Raya Regency Regional Library in realizing a culture of community literacy can be said to have not run as expected. This is based on research that is constrained by the availability of budget funds and human resources. The research data was obtained from the results of observations and interviews with purposively selected research subjects. This type of descriptive research with a qualitative approach, the results of the research, the Kubu Raya Regency Regional Library has not played a role in realizing a culture of community literacy. This can be seen in the role of a Facilitator where the Regional Library has not been able to facilitate several facilities and infrastructure that support in realizing a literacy culture in several school libraries and Community Reading Gardens (TBM) in Kubu Raya Regency. Meanwhile, the role of Community Servant has been carried out according to its provisions. The role as a companion who is actually a partner in realizing a literacy culture based on the research results of the existing companions has never received training in any form so as to affect the ability as a companion. As a Partner, regional libraries have not fully carried out their role in fostering, supporting and collaborating in an effort to improve the literacy culture of the community with existing literacy enthusiasts. Meanwhile, the role as a funder, the regional library does not provide assistance in the form of funds but as an intermediary in literacy activists asking for assistance from the national library. Based on the results of the research, it is recommended: as a facilitator, regional libraries can innovate in accordance with their duties and responsibilities, as a companion can provide motivation, support and inspiration for literacy seekers. As a partner, regional libraries can partner with the private sector and play a role as Funders, due to their limitations, libraries can focus on important activities that have an impact on realizing a culture of community literacy